2009
DOI: 10.1186/1471-2458-9-285
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and mental illness: results from population surveys in Australia and the United States

Abstract: Background: Smoking has been associated with a range of mental disorders including schizophrenia, anxiety disorders and depression. People with mental illness have high rates of morbidity and mortality from smoking related illnesses such as cardiovascular disease, respiratory diseases and cancer. As many people who meet diagnostic criteria for mental disorders do not seek treatment for these conditions, we sought to investigate the relationship between mental illness and smoking in recent population-wide surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
363
1
13

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(401 citation statements)
references
References 67 publications
24
363
1
13
Order By: Relevance
“…Also, smokers in the USA that experienced high levels of psychological distress smoked more cigarettes per day and smoking rates varied according to type of mental disorder. Smoking prevalence was 21.3% among those with no mental disorder compared to 37.8% in people with anxiety disorders, 45.1% in those with mood disorders, and 63.6% among adults with substance use disorders 8 .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Also, smokers in the USA that experienced high levels of psychological distress smoked more cigarettes per day and smoking rates varied according to type of mental disorder. Smoking prevalence was 21.3% among those with no mental disorder compared to 37.8% in people with anxiety disorders, 45.1% in those with mood disorders, and 63.6% among adults with substance use disorders 8 .…”
Section: Introductionmentioning
confidence: 89%
“…In Australia, a study showed that prevalence is higher among patients with severe mental illness than in people with general mental illness (51.2% and 26.4%, respectively) 7 , while in Canada smoking prevalence was 51.8% in patients with schizophrenia compared to 39.2% among those with mood disorder or anxiety 6 . A more recent study of a nationally representative probability sample of 9,282 people in the USA showed that adults affected by a mental disorder in the past 12 months smoked almost twice as much as adults without mental disorders 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In light of increased rates of smoking in mood disorders (Lasser et al, 2000;Lawrence et al, 2009) and emerging findings of the effects of nicotine on striatal functions (Exley et al, 2013), our results could be influenced by smoking status.…”
Section: Limitationsmentioning
confidence: 96%
“…A substantial proportion of all smokers have a history of depression, and among people with depression, smoking prevalence is about twice as high as in the general population [1][2][3], leading to increased morbidity and premature mortality [4][5][6].…”
Section: Introductionmentioning
confidence: 99%